Permission to feel : unlocking the power of emotions to help our kids, ourselves, and our society thrive - Brackett, Marc A. (New York : Celadon Books, 2019)
"Marc Brackett is a professor in Yale University's Child Study Center and founding director of the Yale Center for Emotional Intelligence. In his 25 years as an emotion scientist, he has developed a remarkably effective plan to improve the lives of children and adults -- a blueprint for understanding our emotions and using them wisely so that they help, rather than hinder, our success and well-being. The core of his approach is a legacy from his childhood, from an astute uncle who gave him permission to feel. He was the first adult who managed to see Marc, listen to him, and recognize the suffering, bullying, and abuse he'd endured. And that was the beginning of Marc's awareness that what he was going through was temporary. He wasn't alone, he wasn't stuck on a timeline, and he wasn't "wrong" to feel scared, isolated, and angry. Now, best of all, he could do something about it."--Amazon.
Prologue -- Permission to feel. Permission to feel ; Emotions are information ; How to become an emotion scientist -- The RULER skills. R: recognizing emotion ; U: understanding emotion ; L: labeling emotion ; E: expressing emotion ; R: regulating emotion -- Applying emotion skills for optimum well-being and success. Emotions at home ; Emotions at school: from preschool to college ; Emotions at work -- Creating an emotion revolution.
Includes bibliographical references (pages 243-285).
Keywords: Emotional intelligence; Emotions; Well-being.